Regeneration of Exhausted Ion Exchanger Resins Used in Water Treatment - Khalkhali, R.A.; Chaichi, M.H.; Mahmoodloo, R.; Sofla, H.G. (Asian Journal of Chemistry, 2016)
The regeneration of the two types of used resins (anionic and cationic), employing different acid, base and NaCl solutions, was investigated. The most efficient solutions for the regeneration of the used resins with the least pollution were found to be a mixture of HCl (5% w/v) + NaCl (10% w/v) for strong cationic resins and NaOH (3% w/v) + NaCl (10% w/v) for strong anionic resins.